Direct Two-Minute Unassisted Breathing Evaluation (DTUBE) is an Attractive Alternative to Longer Spontaneous Breathing Trials: A Prospective Observational Study. Issue 3 (March 2017) - Bloom, Matthew B.; Lu, Jonathan; Tran, Tri; Bukur, Marko; Chung, Rex; Ley, Eric J.; Melo, Nicolas; Salim, Ali; Margulies, Daniel R.
We sought to identify a simple bedside method to predict successful extubation outcomes that might be used during rounds. We hypothesized that a direct 2-minute unassisted breathing evaluation (DTUBE) could replace a longer spontaneous breathing trial (SBT). Data were pro-spectively collected on all patients endotracheally intubated for >48 hours nearing extubation in a tertiary center's mixed trauma/surgical intensive care unit from August 2012 to August 2013. The SBT was performed for at least 30 minutes at 40 per cent FiO2, PEEP 5, and PS 8. DTUBE was performed by physically disconnecting the intubated patient from the ventilator circuit for a 2-minute period of direct observation on room air. Successful extubation was defined freedom from ventilator for greater than 72 hours. Both SBTand DTUBE were performed 128 times, resulting in 90 extubations. The DTUBE correctly predicted success in 75/79 (94.9%) extubations versus 82/89 (92.1%) via SBT. No adverse effects were directly attributed to the DTUBE. The DTUBE is a rapid method of evaluating patients for extubation with prediction accuracy similar to the SBT.